Chloroplast- or Mitochondria-Targeted DEAD-Box RNA Helicases Play Essential Roles in Organellar RNA Metabolism and Abiotic Stress Responses - Nawaz, Ghazala; Kang, Hunseung (Frontiers in Plant Science, 2017)
The yields and productivity of crops are greatly diminished by various abiotic stresses, including drought, cold, heat, and high salinity. Chloroplasts and mitochondria are cellular organelles that can sense diverse environmental stimuli and alter gene expression to cope with adverse environmental stresses. Organellar gene expression is mainly regulated at posttranscriptional levels, including RNA processing, intron splicing, RNA editing, RNA turnover, and translational control, during which a variety of nucleus-encoded RNA-binding proteins (RBPs) are targeted to chloroplasts or mitochondria where they play essential roles in organellar RNA metabolism. DEAD-box RNA helicases (RHs) are enzymes that can alter RNA structures and affect RNA metabolism in all living organisms. Although a number of DEAD-box RHs have been found to play important roles in RNA metabolism in the nucleus and cytoplasm, our understanding on the roles of DEAD-box RHs in the regulation of RNA metabolism in chloroplasts and mitochondria is only at the beginning. Considering that organellar RNA metabolism and gene expression are tightly regulated by anterograde signaling from the nucleus, it is imperative to determine the functions of nucleus-encoded organellar RBPs. In this review, we summarize the emerging roles of nucleus-encoded chloroplast- or mitochondria- targeted DEAD-box RHs in organellar RNA metabolism and plant response to diverse abiotic stresses.